2002
DOI: 10.1152/ajpheart.00427.2001
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent postextrasystolic potentiation and Ca2+ recirculation fraction in canine hearts

Abstract: . Temperature-dependent postextrasystolic potentiation and Ca 2ϩ recirculation fraction in canine hearts. Am J Physiol Heart Circ Physiol 282: H403-H413, 2002; 10.1152/ajpheart.00427.2000.-We have found that cardiac temperature proportionally changes O2 cost of contractility, defined as O2 consumption for myocardial total Ca 2ϩ handling normalized to contractility in terms of the end-systolic pressure-volume ratio (maximal elastance, Emax), in the canine left ventricle (temperature sensitivity, Q10 ϭ 2). We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
22
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 38 publications
11
22
1
Order By: Relevance
“…We obtained RF at 33°C, 36°C, and 38°C while eliminating the temperature-dependent changes in peak isovolumic LVP of the regular beats by adjusting LVV. The present results yielded essentially the same temperature dependence of RF as the previous study [14], i.e., whether or not we changed LVV to compensate for the temperature-dependent LVP. The present results validated our present hypothesis.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…We obtained RF at 33°C, 36°C, and 38°C while eliminating the temperature-dependent changes in peak isovolumic LVP of the regular beats by adjusting LVV. The present results yielded essentially the same temperature dependence of RF as the previous study [14], i.e., whether or not we changed LVV to compensate for the temperature-dependent LVP. The present results validated our present hypothesis.…”
supporting
confidence: 86%
“…Therefore, it remains unknown whether the temperature-dependently decreased LVP at a constant LVV affected the temperature-dependent RF. Based on our previous results [13,14], we hypothesized that the temperature-dependent RF would primarily be due to the temperature effect per se rather than the simultaneously changed peak LVP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At these physiological beat intervals, RF increases as the beat interval shortens [17] in contrast to the constant RF independent of beat intervals longer than the period of full mechanical restitution [20,21,27,28]. At present, we are not interested in such relatively long beat intervals because we have to obtain RF at the shorter beat intervals we consistently observe in our cardiac mechanoenergetics experiments [7][8][9][10][11][12]22].…”
Section: Discussionmentioning
confidence: 91%
“…Here, we used aϭ0.5, e ϭ2, and s ϭ0.8 as the representative values for regular beat intervals of 400-600 ms and extrasystolic beat intervals of 300-400 ms in our previous observations [11,12,17]. Furthermore, we increased b from 0 in steps of 0.1 and stopped it at 0.5 (ϭa) although our previous observations have shown that alternans PESPs obviously have bՆa [11,12,17]. In other words, PESPs with bϾa appeared so obvious that no one would dare to fit an exponential curve to it.…”
Section: Methodsmentioning
confidence: 99%